Defining and averting syndemic pathways in aquaculture: a major global food sector - Stentiford, Grant D.; Tyler, Charles R.; Ellis, Robert P.; Bean, Tim P.; MacKenzie, Simon; Brugere, Cecile; Holt, Corey C.; Peeler, Edmund J.; Christison, Kevin W.; Rushton, Jonathan; Bass, David (Frontiers in Sustainable Food Systems, 2023)
Aquaculture now provides half of all aquatic protein consumed globally – with most current and future production occurring in low- and middle-income countries (LMIC). Concerns over availability and application of effective policies to deliver safe and sustainable future supply, have potential to hamper further development of the sector. Creating healthy systems must extend beyond simple exclusion of disease agents to tackling the host-, environmental-, and human- drivers of poor outcomes and to building new policies which incorporate these broader drivers. Syndemic theory provides a potential framework for operationalising this One Health approach.